2020
DOI: 10.3390/foods9081045
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Components, Microbial Metabolites and Human Health: Reading between the Lines

Abstract: Trillions of bacteria reside in the human gut and they metabolize dietary substances to obtain nutrients and energy while producing metabolites. Therefore, different dietary components could affect human health in various ways through microbial metabolism. Many such metabolites have been shown to affect human physiological activities, including short-chain fatty acids metabolized from carbohydrates; indole, kynurenic acid and para-cresol, metabolized from amino acids; conjugated linoleic acid and linoleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 180 publications
(209 reference statements)
0
5
0
Order By: Relevance
“…The gut flora plays a key role in host energy metabolism (Guarner and Malagelada, 2003;Dai et al, 2011;Pérez-Cobas et al, 2013). Indigestible carbohydrates are degraded by fermentation of colonic microflora to produce metabolic end products, such as SCFAs, these metabolites have been shown to affect host physiological activities (Topping and Clifton, 2001;Wong et al, 2006;Wang et al, 2019;Guo et al, 2020). Recent studies have confirmed that SCFAs can inhibit the production of anti-inflammatory factors and inhibit colonic inflammation (Tan et al, 2014;van der Beek et al, 2017;Kurata et al, 2019;Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The gut flora plays a key role in host energy metabolism (Guarner and Malagelada, 2003;Dai et al, 2011;Pérez-Cobas et al, 2013). Indigestible carbohydrates are degraded by fermentation of colonic microflora to produce metabolic end products, such as SCFAs, these metabolites have been shown to affect host physiological activities (Topping and Clifton, 2001;Wong et al, 2006;Wang et al, 2019;Guo et al, 2020). Recent studies have confirmed that SCFAs can inhibit the production of anti-inflammatory factors and inhibit colonic inflammation (Tan et al, 2014;van der Beek et al, 2017;Kurata et al, 2019;Zeng et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in metabolite levels in a person are affected by many factors, including genetics, the environment, and dietary intake [117]. The type of diet is not only directly responsible for the metabolites but also indirectly via nutritional changes inflicted upon the gut microbial and thereby their own metabolism [117,118].…”
Section: The Impact Of Food Metabolites On Human Healthmentioning
confidence: 99%
“…The changes in metabolite levels in a person are affected by many factors, including genetics, the environment, and dietary intake [117]. The type of diet is not only directly responsible for the metabolites but also indirectly via nutritional changes inflicted upon the gut microbial and thereby their own metabolism [117,118]. In recent years, more evidence has surfaced proving that many aspects of human health are affected by the gut microbiota such as obesity-associated disorders, regulation of blood pressure, and the immunity of the host to pathogens [119][120][121].…”
Section: The Impact Of Food Metabolites On Human Healthmentioning
confidence: 99%
“…The macronutrient emphasis of microbiome research focuses on high sugar, high fat and low fiber diet effects on the microbiome [3]. Changes in levels of these macronutrients leading to changes in immune function, dysbiosis, intestinal permeability and microbial translocation are being observed [36,37]. The PHM hypothesis includes the macronutrient role, but emphasizes how macronutrients might affect the abundance of PHMs.…”
Section: Foundations Of the Phm Hypothesis And Comparison With Other mentioning
confidence: 99%